2006
DOI: 10.1016/j.bbaexp.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A novel Xenopus laevis larval keratin gene, xlk2: Its gene structure and expression during regeneration and metamorphosis of limb and tail

Abstract: A novel cytokeratin (CK) gene, xlk2, was cloned from a cDNA library prepared from regenerating limbs of Xenopus larvae. The deduced amino acid sequence indicated that its product, XLK2, is a 48 kDa type I (acidic) CK and has a high similarity to CK13, 15, and 19 with the highest homology (58%) to mouse CK15. The gene of xlk2 exclusively expressed in basal cells of the bi-layered larval epidermis, but not in other cells in larvae and not in other periods of life. Its expression was down-regulated during spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the tail region, the maturation of basal cells never occurs and thus the tail epidermis fails to remodel into adult counterparts. We have previously analyzed the expression profiles of several larval-and adult-type specific keratin genes in Xenopus laevis and Rana catesbeiana during spontaneous and TH-induced metamorphosis Watanabe et al 2001Watanabe et al , 2002Suzuki et al 2002;Tazawa et al 2006). Among these keratin genes, Xenopus Adult Keratin-C (xak-c) is exclusively expressed in epidermal basal cells during Xenopus metamorphosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the tail region, the maturation of basal cells never occurs and thus the tail epidermis fails to remodel into adult counterparts. We have previously analyzed the expression profiles of several larval-and adult-type specific keratin genes in Xenopus laevis and Rana catesbeiana during spontaneous and TH-induced metamorphosis Watanabe et al 2001Watanabe et al , 2002Suzuki et al 2002;Tazawa et al 2006). Among these keratin genes, Xenopus Adult Keratin-C (xak-c) is exclusively expressed in epidermal basal cells during Xenopus metamorphosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, in amphibians, such keratin gene expression patterns have not been described. There are several reports of keratin expression in amphibians (Ferretti et al, 1989(Ferretti et al, , 1991(Ferretti et al, , 1993Tsonis et al, 1992a,b;Ferretti, 1997, 1999;Ferretti and Ghosh, 1997;Tazawa et al, 2006). At least three antibodies recognize WE (and normal keratinocytes) (WE3, 4, and 6).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sequence analyses revealed that the subdomain organization was basically identical to that of mammalian and fish keratins in the central rod domain, detecting the four consecutive coils 1A, 1B, 2A, and 2B [ 3 , 9 , 12 , 21 , 39 ]. Moreover, both sseKer1 and sseKer2 presented the IF signature motif at the end of coil 2B, a feature that is common to all IFs, and possessed a predicted molecular mass and pI within the expected value for vertebrate type I keratins [ 1 , 19 , 21 , 23 , 33 , 34 , 39 - 41 ]. A leucine-zipper motif conserved among type I keratins from zebrafish, goldfish ( Carassius auratus ), rainbow trout ( Oncorhynchus mykiss ), X. laevis , and human was also identified at the end of coil 1B in both keratins [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, type II xlk was expressed exclusively in the larval skin, and type I xak-a , xak-b , and xak-c genes in adult skin [ 34 , 35 ]. Finally, xlk2 , another type I keratin gene, was exclusively expressed in the larval period from hatching to late metamorphic stages [ 41 ]. In developmental studies of Rana catesbeiana tadpoles, three epidermally expressed keratins have been further characterized: rlk and rk8 (type II), and rak (type I).…”
Section: Discussionmentioning
confidence: 99%